Mexico - Stads, Gert-Jan; López, Georgel Moctezuma; Espinosa García, José Antonio; Cuevas Reyes, Venancio; Jolalpa Barrera, José Luis (International Food Policy Research Institute, 2008)
Quantitative data are important in measuring, monitoring, and benchmarking the inputs, outputs, and performance of agricultural science and technology (S&T) systems. They are an indispensable tool when it comes to assessing the contribution of agricultural S&T to agricultural growth and, more generally, economic growth. S&T indicators assist research managers and policymakers in policy formulation and decision-making on strategic planning, priority setting, monitoring, and evaluation. They also provide information to government and other institutions (e.g., policy research institutes, universities, and the private sector) involved in the public debate on the state of agricultural S&T at national, regional, and international levels. This brief reviews the major investment, capacity, and institutional trends in public agricultural research in Mexico since 1981, using recent data collected under the Agricultural Science and Technology Indicators (ASTI) initiative (IFPRIINIFAP 2007-08) and underlying data sets of an unpublished report by Beintema et al. (2001)